Revascularization for controlling hypertension and improving cardiorenal failure in Leriche syndrome. (9th July 2022) - Takagi, Sho; Hirano, Keisuke; Nakasu, Akio; Yanagisawa, Junji; Goto, Yoshihiro; Okawa, Yasuhide
Abstract: Leriche syndrome usually occurs when atherosclerotic obstructions result in luminal narrowing of the abdominal aorta or iliac arteries and leads to thrombosis; it rarely causes heart or renal failure. We report the case of a 58‐year‐old Asian man with heart and renal failure as the dominant clinical manifestations of renovascular hypertension caused by Leriche syndrome. We performed an aorto‐bifemoral bypass and unilateral renal artery stenting. Post‐operative echocardiography showed improved cardiac function, with the left ventricular ejection fraction increasing from 30% before surgery to 54.2% after surgery. Moreover, his heart rate and blood pressure became stable, and his serum creatinine and brain natriuretic peptide levels decreased from 3.46 to 1.08 mg/dL and 685 to 4 pg/mL, respectively. Our case report shows that aorto‐bifemoral bypass and unilateral renal artery stenting can effectively treat heart and renal failure resulting from renovascular hypertension caused by Leriche syndrome.